2009
DOI: 10.1080/08860220802595476
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin and Uremic Pruritus in Hemodialysis Patients

Abstract: Gabapentin is an effective agent in treating uremic pruritus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(79 citation statements)
references
References 18 publications
4
72
0
3
Order By: Relevance
“…53,[96][97][98] In a double-blind, crossover, RCT of 25 HD patients assigned to gabapentin 300 mg by mouth after dialysis or placebo, pruritus intensity significantly improved with gabapentin but not with placebo. 53 Similarly, in a double-blind, placebo-controlled trial of 34 HD …”
Section: Peripheral Neuropathy Treatmentmentioning
confidence: 99%
“…53,[96][97][98] In a double-blind, crossover, RCT of 25 HD patients assigned to gabapentin 300 mg by mouth after dialysis or placebo, pruritus intensity significantly improved with gabapentin but not with placebo. 53 Similarly, in a double-blind, placebo-controlled trial of 34 HD …”
Section: Peripheral Neuropathy Treatmentmentioning
confidence: 99%
“…Razeghi i wsp. [15] zaobserwowali, że większe stężenie ferrytyny oraz zmniejszone stężenie albumin i transferyny u pacjentów z PChN wiązało się z występowaniem bardziej nasilonego świądu [15]. Świąd najczęściej obejmuje skórę pleców, ramion, przedniej powierzchni klatki piersiowej oraz twarzy [2,4,6,7,12].…”
Section: Nieswoiste Zmiany Skórne U Pacjentów Ze Schyłkową Niewydolnounclassified
“…The pathogenesis of CKD-associated pruritus involves a number of factors including xerosis, hypervitaminosis A, electrolyte disorders (hypercalcaemia, hyperphosphataemia, hypermagnesaemia), secondary hyperparathyroidism, peripheral neuropathy and increased plasma concentrations of β-endorphins, μ-receptor antagonists, interleukin 2 (IL-2), IL-6, C-reactive protein (CRP), and elevated mast cell count in the skin [2,3,6,[9][10][11][12][13][14]. Razeghi et al [15] showed that increased ferritin levels and reduced albumin and transferrin levels in patients with CKD were associated with more severe skin itch [15]. Pruritus typically affects the skin on the back, shoulders, anterior surface of the chest and face [2,4,6,7,12].…”
Section: Nieswoiste Zmiany Skórne U Pacjentów Ze Schyłkową Niewydolnomentioning
confidence: 99%
“…2 to 5.7 Several mechanisms are cited in attempting to explain this event, such as hyperparathyroidism, 14,16,20 allergic reactions, proliferation of mast cells in the skin, iron deficiency anemia, hypervitaminosis A, xerosis, neuropathy , cytokines, bile acids, nitric oxide, electrolyte [2][3][4]21 , creatinine, total protein 5.8 , urea, ferritin, and transferrin disorders and 8 alterations of the immune system. 22 Many authors believe that altered levels of magnesium, parathyroid hormone, phosphorus, calcium and calcium/phosphorus ratio are involved in renal pruritus.…”
Section: Introductionmentioning
confidence: 99%
“…The symptom that most frequently affects these patients is pruritus, [2][3][4][5][6][7][8][9][10][11][12] ranging between 22% and 90% in prevalence. [1][2][3][4][6][7][8][9][13][14][15] It often begins six months before the start of dialysis and manifests itself in markedly different ways; it may be persistent, intense and widespread or just localized and transient. 4.14 Pruritus causes changes in quality of life and 11 has a physical and mental impact, which contribute to depression, agitation, sleep disturbances and fatigue.…”
Section: Introductionmentioning
confidence: 99%